Evaluation of N fertilization management strategies for increasing crop yields and nitrogen use efficiency in furrow-irrigated maize–wheat system under permanent raised bed planting. Issue 9 (28th July 2020) - Sandhu, Opinder Singh; Gupta, RK; Thind, Harmeet Singh; Jat, Mangi Lal; Singh, Yadvinder-; Sidhu, Harminder Singh
ABSTRACT: Information on the effect of N management on crop yields and N use efficiency (NUE) under furrow irrigations is scarce for conservation agriculture (CA)-based annual maize–wheat (MW) system in South Asia. A 2-year (2013–2015) field experiment was conducted to evaluate the effects of residue management in main plots and combinations of two rates and three methods of N fertilizer application plus no N control treatment in subplots on the yield, N uptake and NUE of permanent raised bed (PB) MW system in north-western India. Residue retained on surface significantly increased grain yields by 7.7% and 4.3% in maize and wheat compared to no residue, respectively. Results showed that while uniformly broadcast method (B) required 120 kg N ha −1, similar maize and wheat yields can be achieved with 90 kg N ha −1 using deep placement on beds (DB) thereby saving 30 kg N ha −1 . DB increased maize yield by 5.4% and 10.9% compared with DF and B, respectively. In wheat, DB and DF significantly increased grain yield by 4–7% compared to B. At 120 kg N ha −1, NUE of 61% and 74% with B was increased to 73% and 98% with DB in wheat and maize, respectively.